A capabilities approach to housing and quality of life: The evidence from Germany - Dermot Coates; Paul Anand; Michelle Norris (The Open University, Economics Department, 2015)
The capabilities approach developed by Sen (1985) and others has been highly influential in development circles and is increasingly being thought of as a theoretical framework suitable for understanding and measuring quality of life issues in high income contexts (Anand et al (2009), EU (2009)). In this paper, we contribute to a growing literature that draws on the approach to help understand connections between housing and quality of life. Specifically, we explore whether a broad range of capabilities and activities associated with housing have a detectable impact on housing satisfaction, and whether housing satisfaction contributes to overall life satisfaction. Our results indicate that housing satisfaction is indeed related to overall life satisfaction and that a wide range of different kinds of variables appear to impact housing satisfaction itself. The paper concludes by suggesting its findings underline the fact that a holistic view of housing policies needs to be taken if such policies are to make a full contribution to improved quality of life.
Keywords: 330; housing satisfaction; capabilities approach; quality of life